Heavy metals potential health risk assessment through consumption of wastewater irrigated wild plants: A case study. Issue 1 (2nd January 2016) - Khan, Muhammad Usman; Muhammad, Said; Malik, Riffat Naseem; Khan, Sabaz Ali; Tariq, Mohammad
ABSTRACT: This study investigates the potential health risk assessment of heavy metals consumption through wild plants (WPs) irrigated with wastewater and fresh water in the Bannu district, Pakistan. Therefore, soil and WP samples were collected and analyzed for heavy metals by atomic absorption spectrophotometer (Varian FAAS-240). Wastewater irrigated soil showed an elevated level for Cd (5.05–14.50 mg/Kg) and Ni (99.35–104.85 mg/Kg), while Cd (3.35–4.84 mg/Kg) concentration in the fresh water irrigated soil also surpassed the maximum allowable limits (MAL) set by the World Health Organization. Similarly, selected wastewater irrigated plants and fresh water irrigated plants also exceeded the MAL set by the Food and Agriculture Organization for Cd, Pb, and Cr (except for Cr in Vicia sativa ). Heavy metal concentrations through WPs consumption were evaluated for the health risk index (HRI). The HRI value for each selected WPs was <1. However, total HRI values through WPs consumption was >1. Therefore, WPs consumption of the study area may pose a potential threat to the local community.